-16
Пошаговое объяснение:
Задание
Вычислить:
5х - 3Iу+1I + Iу-1I при х = -2, у = -5
Решение
1) 5х при х = -2 равно:
5 · (-2) = - 10.
2) I у + 1 I при у = -5 равен:
I -5 + 1 I = I - 4 I = 4 - согласно определению "модуля" (модуль отрицательного числа есть число положительное);
3) I у - 1 I при у = -5 равен:
I -5 -1 I = I - 6 I = 6 - согласно определению "модуля" (модуль отрицательного числа есть число положительное).
Таким образом:
5х - 3·Iу+1I + Iу-1I при х = -2, у = -5 равно:
5· (-2) - 3·I-5+1I + I-5-1I = - 10 - 3·4 + 6 = -10 - 12 + 6 = -22 +6 = -16
ответ: -16
Пошаговое объяснение: